Investigation of wood fire resistance mechanism in modifying by impregnating agents - Цапко, Юрий Владимирович (Technology audit and production reserves, 2014)
Application of the modifiers for wood surface treatment is considered and some results of our research in this field are given in the paper. The main purpose of the research is to investigate the mechanism of thermal decomposition of wood and effect of modification on the thermal degradation. The process of thermal degradation of modified wood by chromatography was studied. The qualitative and quantitative analysis of the obtained products was carried out. Coke residue in the treated samples was increased by 4 times and the amount of flammable gases was reduced, in particular for wood, treated with a mixture of ammonium phosphate and sulphate the amount of nitrogen was increased by more than 80 times, for wood treated with a mixture of sodium carbonate and boric acid, carbon dioxide was increased by 1.5 times, and for wood treated with a mixture of sodium orthoborate and boric acid – more than 10% of flammable gases, the amount of carbon dioxide was slightly increased. The research results can be applied in the development of effective modifiers and in the determination of operational conditions of wooden structures.